The Use Of Grammatical and Lexical Cohesion In Short Story â€œNyanyian Pilu Meo Oni yang Terdengar dari Hutanâ€ By Lita Lestianti - Yuke Elvin Herawati; Dwi Susanti Khoirun Nisa'; Rizky Fitriyanti Pradani; Muhammad Arifin; Sri Utami (Universitas Muria Kudus, 2025)
The short story studied in this study is